On Modified Weighted Exponential Rayleigh Distribution - Khalid Hussein, Lamyaa; Hasan Hussein, Iden; Abdullah Rasheed, Huda (Al-Nahrain Journal of Science, 2024)
This study seeks for classical estimations to estimating the anonymous parameters and reliability function of Modified Weighted Exponential Rayleigh  distribution. These classical methods are chosen precisely because all of these methods maximize the probability density function. Newton-Raphson technique was used to derive estimation methods.